2017
DOI: 10.1007/s11302-017-9588-x
|View full text |Cite
|
Sign up to set email alerts
|

POM-1 inhibits P2 receptors and exhibits anti-inflammatory effects in macrophages

Abstract: Extracellular nucleotides can modulate the immunological response by activating purinergic receptors (P2Rs) on the cell surface of macrophages, dendritic, and other immune cells. In particular, the activation of P2X7R can induce release of cytokines and cell death as well as the uptake of large molecules through the cell membrane by a mechanism still poorly understood. Polyoxotungstate-1 (POM-1) has been proposed as a potent inhibitor of ecto-nucleotidases, enzymes that hydrolyze extracellular nucleotides, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…DMSO, present in the wells even in 10% ( v / v ), did not significantly influence the activity of CD39 and CD73. POM-1, an inhibitor of E-NTPDase1-3 enzymes [ 30 ] ( Table 1 ) and antagonist of some P2 purinergic receptors [ 31 ], significantly but incompletely reduced the activity of CD39. Interestingly, POM-1 also inhibited CD73, at least to the same extent as it inhibited CD39.…”
Section: Resultsmentioning
confidence: 99%
“…DMSO, present in the wells even in 10% ( v / v ), did not significantly influence the activity of CD39 and CD73. POM-1, an inhibitor of E-NTPDase1-3 enzymes [ 30 ] ( Table 1 ) and antagonist of some P2 purinergic receptors [ 31 ], significantly but incompletely reduced the activity of CD39. Interestingly, POM-1 also inhibited CD73, at least to the same extent as it inhibited CD39.…”
Section: Resultsmentioning
confidence: 99%
“…Pimenta-Dos-Reis reported that POM-1 inhibits activation of macrophages in mice with sepsis induced by lipopolysaccharide and reduces the levels of related cytokines [ 30 ]. This finding indicates that the effect of POM-1 on the activation or differentiation of TAMs may differ according to the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal macrophages were obtained by lavage of the peritoneal cavity with 10 ml of Dulbecco's modified Eagle medium (DMEM; Gibco, USA). After isolation from the peritoneal cavity, the monocytes-macrophages pass through an adhesion process and need to be maintained in culture for at least 3 days for stabilization (57). The number of total viable cells of mice, infected with T. muris or not, was determined using trypan blue (Sigma-Aldrich) in a Neubauer chamber.…”
Section: Fig 13mentioning
confidence: 99%